Combinational detection of autolysin and penicillin-binding protein 2B genes of Streptococcus pneumoniae by PCR. - Ubukata, K (1996)
PCR was used to identify penicillin resistance in 1,062 clinical isolates of Streptococcus pneumoniae. Three sets of primers were designed to amplify (i) a 240-bp fragment of the penicillin-binding protein (PBP) 2B gene (pbp2b) of penicillin-susceptible S. pneumoniae (PSSP), (ii) a 215-bp fragment of the class A mutations of the pbp2b gene present in penicillin-resistant S. pneumoniae, and (iii) a 286-bp fragment of the class B mutation. In addition, a set of primers that amplify 273 bp of the autolysin (lytA) gene was applied in combination with the above to identify S. pneumoniae. Of 621 isolates for which MICs of penicillin were < or = 0.06 mu g/ml, 614 (98.9%) were ascertained as having DNA fragments amplified by the PSSP primers. Of 441 isolates for which MICs of penicillin were > or = 0.125 mu g/ml, a class A mutation was detected in only 8 (1.8%), a class B mutation was detected in 310 (70.3%), and neither class A nor class B mutations were found in the remaining 123 (27.9%). However, when analysis was limited to isolates for which MICs of penicillin were > or = 1.0 mu g/ml, 247 isolates (89.8%) of 275 were found to possess a class B mutation. When PBPs were analyzed in 12 isolates with unclear mutations of the pbp2b gene by using [3H]benzylpenicillin, low affinity to PBP 2B was observed in them all. These findings suggest that a pbp2b mutation other than class A or class B is present in these isolates. These results also indicate that it may be possible to identify PSSP and penicillin-resistant S. pneumoniae by applying PCR using a combination of primers to detect the susceptible pbp2b gene, resistant pbp2b gene mutations, and the lytA gene.